2005
DOI: 10.1210/jc.2005-0110
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Parallel Randomized, Double-Blind, Double-Dummy Controlled Clinical Trial Comparing Clomiphene Citrate and Metformin as the First-Line Treatment for Ovulation Induction in Nonobese Anovulatory Women with Polycystic Ovary Syndrome

Abstract: Six-month metformin administration is significantly more effective than six-cycle CC treatment in improving fertility in anovulatory nonobese PCOS women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
134
2
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(154 citation statements)
references
References 36 publications
8
134
2
9
Order By: Relevance
“…In the present study, a significant difference was found in cumulative pregnancy rate between metformin and clomiphene group 60% versus 33.3%; P = 0.02 which goes in accordance with Palomba 19 . Their study showed that, over six months of treatment a significant difference was observed in the cumulative pregnancy rate (68.9% vs 34% in metformin and CC group respectively; (P<0.001).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, a significant difference was found in cumulative pregnancy rate between metformin and clomiphene group 60% versus 33.3%; P = 0.02 which goes in accordance with Palomba 19 . Their study showed that, over six months of treatment a significant difference was observed in the cumulative pregnancy rate (68.9% vs 34% in metformin and CC group respectively; (P<0.001).…”
Section: Discussionsupporting
confidence: 89%
“…These data disagree with an our previous head-to-head RCT [11] comparing metformin with CC, which demonstrated that, in an infertile non-obese PCOS population, metformin is equally as effective as CC for inducing ovulation but is superior in terms of pregnancy rate.…”
contrasting
confidence: 99%
“…The administration of metformin induces ovulatory cycles in anovulatory CC-resistant or non-resistant patients with PCOS and improves the ovulation rate as an additional treatment in women who received CC [10,11].…”
mentioning
confidence: 99%
“…Short term use of metformin resulted in 25% ovulation [25]. In another short term study, 12 week use of metformin led to 73% ovulation [26].But 6 month use of metformin resulted in 62.9% [27], 55.4% ovulation [28].…”
Section: Introductionmentioning
confidence: 95%